Rodeo as refuge, rodeo as rebellion : gender, race, and identity in the American rodeo - Ford, Elyssa (University Press of Kansas, 2020)
"While much of the recent research on rodeos emphasizes the more well-known Western rodeo with its primarily white, male contestants, men and women of many racial backgrounds and of various identities have played a role in the growth of the rodeo and developed different relationships with the sport. In Rodeo as Refuge, Rodeo as Rebellion: Race, Gender, and Identity in the American Rodeo, Elyssa Ford examines rodeo in Mexican American, Hawaiian, Native American, African American, and LGBTQ+ communities to argue for rodeo as a site of diverse, dynamic cultural performance. In addition to issues of race, gender, ethnicity, and sexuality, Ford also uses questions about sport, history, memory, and identity to explore the commonalities and key differences among specialized rodeo communities, how they developed, and why they've continued despite changes in American culture and society. Ultimately, Ford establishes that rodeo is a place where the past is performed, reproduced, and invented"--